Kites: oxford literacy web - Macdonald, Fiona (Oxford University Press Oxford, 1999)
Looks at where kites originated from, the various types and design, kites as a sport, and festivals. Includes step-by-step instructions on how to make your own kite. Suggested level: junior, primary